Symmetric Telecom Regulation, Competition and Investment - Henten, Anders; Falch, Morten (Nordic and Baltic Journal of Information & Communications Technologies, 2020)
Symmetric telecoms regulation, where it is not only the operators with significant market power (SMP) at national or large geographical scales which are subject to special access obligations, has been on the agenda for long. However, emphasis has hitherto been on asymmetric regulation, but during the past few years, symmetric regulation has gradually gained weight in different EU countries, and the new European Electronic Communications Code also aims at putting more emphasis on symmetric regulation. The paper identifies the reasons behind symmetric access regulation possibly coming to play a more prominent role in EU telecoms regulation, the scope of symmetric regulation and how it is being articulated, and what the possible implications of symmetric regulation could be on the level of investment. The contribution of the paper is to discuss these different elements of understanding the potential role of symmetric regulation.